Integration Analysis Of Islamic Accounting Information System In Payroll And Income Tax Article 21 (Pph 21) Imposition - Bella Nurhudiani; Laylan Syafina (Universitas Trunojoyo Madura, 2023)
This study aims to the application of accounting information systems in payroll and the imposition of income tax article 21 (PPh Article 21) at PT. Putra Dumas Lestari.The research method used is descriptive analysis. Data were obtained through interviews, documentation and literature studies.The results of the study indicate that the applied accounting payroll system is in accordance with the theory, consisting of documents, records, functions and network procedures. The accounting payroll system is quite reliable because it has met the elements of internal control, but there are still some weaknesses in the elements of organizational structure, recording procedures and healthy practices. These weaknesses are dual functions, ineffective recording of attendance and lack of supervision in the process of recording attendance. The results of the study also show that the procedure for calculating Article 21 Income Tax is in accordance with tax regulations. Non-taxable income, office costs and tax rates used are also in accordance with tax regulations. However, in terms of calculating gross income, it is not in accordance with tax regulations because it does not add up rounding and tax permits. At PT. Putra Dumas Lestari shows that in the employee payroll calculation system, it is adjusted to the number of absences and employee skills. This is considered less effective if absences are done manually (with employee signatures) and finger scans if a system error occurs. Meanwhile, the imposition of PPh Article 21 on employee salaries has two different systems based on the latest regulations and policies from the government.